2016
DOI: 10.1002/smll.201601657
|View full text |Cite
|
Sign up to set email alerts
|

Local Mechanical Perturbation Provides an Effective Means to Regulate the Growth and Assembly of Functional Peptide Fibrils

Abstract: Mucin 1 (MUC1) peptide fused with Q11 (MUC1-Q11) having 35 residues has previously been shown to form amyloid fibrils. Using time-dependent and high-resolution atomic force microscopy (AFM) imaging, it is revealed that the formation of individual MUC1-Q11 fibrils entails nucleation and extension at both ends. This process can be altered by local mechanical perturbations using AFM probes. This work reports two specific perturbations and outcomes. First, by increasing load while maintaining tip-surface contact, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The hierarchical structures of amyloid fibrils elucidated using X-ray crystallography and solid-state NMR spectroscopy appear to be very stable [125129]; however, amyloid fibrils showed nearly complete denaturation (i.e., depolymerization or dissociation) to monomers or other types of aggregates. External perturbations, including temperature [119, 122], chemical denaturants [130, 131], pressure [65, 66], mechanical perturbation [132], and the presence of additives, including polyphenols [133, 134], destabilized and denatured amyloid fibrils (several tens of kJ mol −1 of a change in Gibbs free energy) (Fig. 9).…”
Section: Aggregation Of Amyloid β Peptides In Membrane Environmentsmentioning
confidence: 99%
“…The hierarchical structures of amyloid fibrils elucidated using X-ray crystallography and solid-state NMR spectroscopy appear to be very stable [125129]; however, amyloid fibrils showed nearly complete denaturation (i.e., depolymerization or dissociation) to monomers or other types of aggregates. External perturbations, including temperature [119, 122], chemical denaturants [130, 131], pressure [65, 66], mechanical perturbation [132], and the presence of additives, including polyphenols [133, 134], destabilized and denatured amyloid fibrils (several tens of kJ mol −1 of a change in Gibbs free energy) (Fig. 9).…”
Section: Aggregation Of Amyloid β Peptides In Membrane Environmentsmentioning
confidence: 99%
“…We investigated the interaction of TGF-β1 and COMP by comparing high-resolution AFM images of the COMP, TGF-β1, and their mixtures after immobilization onto mica(0001) surfaces. Mica(0001) surfaces were chosen as the support because they are atomically flat structures. ,,, In Figure , the characteristic AFM topographical images for all three systems are displayed side-by-side, using the same scanning size of 500 × 500 nm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Mica(0001) surfaces were chosen as the support because they are atomically flat structures. 4,22,28,29 In Figure 1, the characteristic AFM topographical images for all three systems are displayed side-by-side, using the same scanning size of 500 × 500 nm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AFM imaging force is normally kept small to prevent sample damage, people can also apply a higher force to initiate new events. Liu's group used an AFM probe to mechanically cut the amyloid fibrils, which are formed by mucin 1 peptide fused with Q11 (MUC1-Q11), and observed growth of fibrils at the newly exposed termini using in situ AFM [148]. They showed that orientation and length of branched fibrils can be controlled by the nuclei orientation and reaction time.…”
Section: Peptide and Proteinmentioning
confidence: 99%